UPAYA MENINGKATKAN KOMPETENSI KEPALA SEKOLAHDALAM MANAJEMEN BANTUAN OPERASIONAL SEKOLAH (BOS) YANG TRANSPARANSI DAN AKUNTABEL MELALUI MODEL GROW MEDI SEKOLAH BINAAN - Erdita, Erdita (JGK (Jurnal Guru Kita), 2019)
Abstract:Efforts to Improve Principal Competence in School Operational Assistance Management (Bos), which is Transparency and Accountability through the Model of Growing Mediated Schools. Determination of the place of research is based on the main focus of this research is the compilation of School Budget Activities and Budgets (RKAS) and BOS reporting carried out by the Principal as Chair of the BOS Management Team in accordance with the technical guidelines for the use of BOS and to assist School Principals in managerial competencies especially in the BOS financial sector. . Seen from the results of observations, guidance and examination of documents it appears that the average value of the observed aspects gets "Very Good" so that the performance indicators that have been previously determined have been met through the Grow Me method: the principal is more thorough and skilled at checking the BOS reporting documents. To further clarify the development of research results from one cycle to another, the following table and graph are shown comparison between cycles. Keywords:Principal Competence, School Operational Assistance Management, Grow Me Model Abstrak: Upaya Meningkatkan Kompetensi Kepala Sekolah Dalam Manajemen Bantuan Operasional Sekolah (Bos) Yang Transparansi Dan Akuntabel Melalui Model Grow Medi Sekolah Binaan . Penentuan tempat penelitian tersebut didasarkan pada fokus utama penelitian ini adalah peyusunan Rencana Kegiatan dan Anggaran Sekolah (RKAS) dan pelaporan BOS yang dilakukan Kepala Sekolah sebagai Ketua Tim Manajemen BOS sesuai petunjuk teknis penggunaan BOS dan membantu peningkatan profesional Kepala Sekolah dalam kompetensi manajerial khususnya bidang keuangan BOS.Dilihat dari hasil pengamatan, pembimbingan dan pemeriksaan dokumen tampak bahwa nilai rerata aspek yang diamati mendapat nilai œ Amat Baik sehingga indikator kinerja yang telah ditetapkan sebelumnya telah terpenuhi melalui metode Grow Me yakni : kepala sekolah lebih telitidan terampil memeriksa dokumen pelaporan BOS. Untuk lebih memperjelas perkembangan hasil penelitian dari satu siklus ke siklus lainnya, berikut ini ditampilkan tabel dan grafik perbandingan antar siklus. Kata Kunci : Kompetensi Kepala Sekolah, Manajemen Bantuan Operasional Sekolah, Model Grow Me